Reducing the risk of Plasmodium vivax after falciparum infections in co-endemic areas—a randomized controlled trial (PRIMA) - Thriemer, K; Degaga, TS; Christian, M; Alam, MS; Ley, B; Hossain, MS; Kibria, MG; Tego, TT; Abate, DT; Weston, S; Karahalios, A; Rajasekhar, M; et al. (BioMed Central, 2022)
Background Plasmodium vivax forms dormant liver stages that can reactivate weeks or months following an acute infection. Recurrent infections are often associated with a febrile illness and can cause a cumulative risk of severe anaemia, direct and indirect mortality, and onward transmission of the parasite. There is an increased risk of P. vivax parasitaemia following falciparum malaria suggesting a rationale for universal use of radically curative treatment in patients with P. falciparum malaria even in the absence of detectable P. vivax parasitaemia in areas that are co-endemic for both species. Methods This is a multicentre, health care facility-based, randomized, controlled, open-label trial in Bangladesh, Indonesia and Ethiopia. Patients with uncomplicated falciparum malaria, G6PD activity of ≥70% of the adjusted male median (AMM) and haemoglobin levels ≥8g/dl are recruited into the study and randomized to either receive standard schizonticidal treatment plus 7-day high dose primaquine (total dose 7mg/kg) or standard care in a 1:1 ratio. Patients are followed up weekly until day 63. The primary endpoint is the incidence risk of any P. vivax parasitemia on day 63. Secondary endpoints include incidence risk on day 63 of symptomatic P. vivax malaria and the risk of any P. falciparum parasitaemia. Secondary safety outcomes include the proportion of adverse events and serious adverse events, the incidence risk of severe anaemia (Hb<5g/dl and <7g/dl) and/or the risk for blood transfusion, the incidence risk of ≥ 25% fall in haemoglobin with and without haemoglobinuria, and the incidence risk of ≥ 25% fall in haemoglobin to under 7g/dl with and without haemoglobinuria. Discussion This study evaluates the potential benefit of a universal radical cure for both P. vivax and P. falciparum in different endemic locations. If found safe and effective universal radical cure could represent a cost-effective approach to clear otherwise unrecognised P. vivax infections and hence accelerate P. vivax elimination. Trial registration NCT03916003. Registered on 12 April 2019.